HUBUNGAN KERJASAMA TIM DENGAN KINERJA PERAWAT HEMODIALISIS DI RUMAH SAKIT LAVALETTE KOTA MALANG - Lely Ulfariana; Ika Suhartanti (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2023)
One of the factors that affect employee performance is teamwork. In the nursing profession to produce good performance, a professional nurse must be able to cooperate well with fellow nurses or with other health workers in order to fulfill the process of achieving the goals that have been determined. The purpose of this study was to determine the relationship between teamwork and the performance of hemodialysis nurses at Lavalette Hospital, Malang City.This research is included in the type of correlational observational research with a cross sectional approach. With a sample of 30 respondents in the hemodialysis unit of Lavalette Hospital. From the results of the study, it was found that almost all respondents in the Hemodialysis Room of Lavalette Hospital Malang City had cooperation in the mutually supportive category as many as 29 respondents (96.7%). And almost all respondents in the Hemodialysis Room of Lavalette Hospital Malang City had a good category performance of 27 respondents (90%).From the test results using the Spearman's rho test, it was found that the p value <0.05, namely p = 0.001 which means that there is a relationship between Teamwork and the Performance of the Hemodialysis Room Nurse, Lavalette Hospital, Malang City.Through effective and coordinated collaboration, better performance and work performance will be achieved, because there is a positive relationship between performance and cooperation.